Changes in erythrocyte membrane permeability induced by verapamil, chlorpromazine, and their combinations with amphotericin B - Knopik-Skrocka, Agnieszka; Bielawski, Józef; Chowański, Szymon; Walkowiak, Paulina (Biological Letters, 2012)
Hemolysis induced by 2 amphipathic agents, verapamil and chlorpromazine, was investigated in various incubation conditions. Changes in absorbance of erythrocyte suspension were monitored by absorption spectrophotometry at a wavelength of 590 nm. The hemolysis induced by verapamil or chlorpromazine is of the permeability type. The resistance of erythrocytes to verapamil is much higher than their resistance to chlorpromazine. No evident difference is found between human and pig erythrocytes in their resistance to verapamil. Only a small decrease in the rate of hemolysis induced by verapamil is observed in isotonic CaCl2, MgCl2 or K2SO4 solutions, compared to 160 mM KCl (the standard incubation medium). The changes in hemolytic activity of chlorpromazine in the presence of the divalent cations and anions are less evident. No decrease in hemolytic activity of chlorpromazine and verapamil is observed in the sucrose medium. The hemolytic activity of both the agents increases when they act in combination with polyene antibiotic amphotericin B. The results indicate a strong synergy between amphotericin B and verapamil or chlorpromazine. By contrast, a combined effect of verapamil and chlorpromazine on erythrocytes leads to a decrease in their hemolytic activity. This indicates antagonism between verapamil and chlorpromazine.